PPDM OLAHAN IKAN BANDENG DI KECAMATAN KEERA KABUPATEN WAJO, SULAWESI SELATAN - Lendri, Lendri; Husniati, Husniati; Erna, Erna (Jurnal BALIRESO, 2020)
The village Partnertship Development Diagram (PPDB) is a second year activities focusing fordevelopment of guidefish. Problem focus by a partner. (1) MIlk fish processing is still in small scaleand not using modern technology of milk fish processed, (2) Milk fish process produced was not meetstandard issued by the healthy ministry, (3) partner can not yet compete with other competitors, (4)partner have not yet home production in accordance with SNI. The activities of PPDM on second yearnamely: first stage, meeting with the government of Keera District, fishing trainer, partner and PPDMteam. Second stage, meeting for discussing location of house production for partner. Third stage,training about processing of milk fish product. Production house developed 8 X 4 m in size. There aretwo types of product milk fish processing teached namely milk fish boneless and fish bond crackers.Another activity was packing of product by using vacuum scleare.